الأفعال اللازمة لدى مصطفى زغلول سنوسي في الكتاب "البيان عن قضيّة فلسطين": دراسة صرفيّة دلاليّة - Musa, Mahmud Danjuma; Muhammed Bashir, Ismail (SIBAWAYH Arabic Language and Education, 2025)
الملخصتناول الكتاب "البيان عن قضية فلسطين" لمصطفى زغلول سنوسي، الكاتب العربي النيجيري والمدير والمؤسس لمدرسة دار الدّعوة، لاغوس نيجيريا، قضية من القضايا الاجتماعية التي تهم الأمة الإسلامية خاصة والإنسانية عامة. وأبدى فيه المؤلف موقفه الاجتماعي والسياسي ومهارته اللغويّة مستخدما أفعالا لازمة ومتعدية بكثافة لسرد الحقائق العلمية في مشاطرته الأمم العالمية شعوره نحو اضطهادات غير معهودة يتعرض لها الشعب الفلسطيني. فهدف الباحث في هذه المقالة ليس لتصيد أخطاء المؤلف في استخدام الأفعال اللازمة في الكتاب بل لرصد أسلوبه في استعماله الفعل اللازم في إطار من النصوص اللغوية سواء من القرآن والحديث النبويّ أو الاستخدامات المعجمية الصحيحة، مقارنة بما يشبهها من الكتاب لكشف مدى التزام المؤلف بالاستخدامات الفصيحة لبعض الأفعال اللازمة المختارة مع أبنيتها ودلالاتها. وإمكانيّة تحويل الفعل المتعدّي الأصلي إلى اللازم. ولقد وظّف البحث المنهج الوصفي لمعالجة الموضوع. ولتحقيق هذا الهدف، تم تقسيم المقالة إلى أربعة محاور كالآتي: (1) الكلام عن الفعل اللازم في اللغة العربية: (2): علامات الفعل اللازم: (3) أبنية ودلالات الفعل اللازم: (4) دراسة دلاليّة للفعل اللازم في الكتاب "البيان" عن قضية فلسطين. وييدو في الكتاب أن المؤلف موفّق في استعماله الفعل اللازم في إطار من النصوص اللغوية من القرآن والحديث النبويّ أو الاستخدامات المعجمية الصحيحة. وأنّه التزام بالاستخدامات الفصيحة لبعض الأفعال اللازمة المختارة في أبنيتها ودلالاتها. وحوّل بعض الأفعال المتعدية أصلاً إلى اللازمة للغرض الدلالي الذي هو التعميم والإيجاز في مثل قوله:بعد تخريب مدينة أصفهان، وجعل الجماجم التي تصلي وتصوم وتزكي وتحج بكرة وأصيلا. الكلمات المفتاحيّة: الأفعال اللازمة، مصطفى زغلول سنوسي، قضيّة فلسطين، دراسة دلاليّةAbstractThe book "Al-Bayan 'an Qadiyyat Falastin" (The Exposition on the Issue of Palestinian) by Mustafa Zaghloul Sanusi, a Nigerian author, addresses a social issue of concern to the Islamic Ummah (nation) in particular, and to humanity in general. In it, the author expresses his social and political stance and his linguistic skill, utilizing intransitive and transitive verbs extensively to narrate scientific facts while sharing with the international community his feelings regarding the unprecedented persecutions faced by the Palestinians. The researchers’ goal in this article is not to hunt for the author's errors in the use of intransitive verbs in the book, but rather to monitor his style in using the intransitive verb within a framework of linguistic texts, whether from the Qur'an, the Prophet's Hadith, or correct lexicography usages. This monitoring is done by comparing these established usages with similar instances in the book to reveal the extent of the author's adherence to the eloquent uses of certain selected intransitive verbs, along with their structures and connotations. The research employed the descriptive method to address the topic. To achieve this goal, the article was divided into four axes as follows: Axis One: Discussion of the intransitive verb in the Arabic language. Axis Two: Signs/Markers of the intransitive verb. Axis Three: Structures and connotations of the intransitive verb. Axis Four: A semantic study of the intransitive verb in the book "Al-Bayan" on the Palestinian Issue. It appears in the book that the author sometimes converted originally transitive verbs into intransitive ones for the semantic purpose of generalization and conciseness, as in his statement: "After the destruction of the city of Isfahan, and the making of the skulls that pray, fast, pay Zakat and perform Hajj, Day and Night". Keywords: intransitive verbs, Mustapha Zuglool Sanusi, Palestine, Semantics